2020
DOI: 10.3889/oamjms.2020.4746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Denture Retention by Multi-suction Cup and Denture Adhesive

Abstract: AIM: The aim of the study was to compare the retention of two modalities: Multi-suction cup denture, and denture adhesive and to evaluate the change of retention by different time intervals. PATIENTS AND METHODS: Twelve completely edentulous patients were selected. The patients received two dentures: One conventional denture, and the other with multi-suction cups. The retention was measured by a universal testing machine at insertion, 15 min, 30 min, 1 h, 2 h, and 4 h. All values were recorded in Newtons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To address these issues, various studies based on biologically inspired adhesion mechanisms such as mechanical interlocking, capillary forces, and van der Waals forces driven by interfacial interactions are being conducted. , Although the excellent performance of recently developed reversible adhesive materials increases their applicability to wet biological surfaces such as skin and organs, the development of clean, reversible adhesive materials for oral surfaces with complex three-dimensional surfaces, dynamic masticatory activities, and variable wet environments remains a challenge. In particular, conventional technologies for attaching to the oral cavity, such as dentures, rely on chemical adhesive materials, but there is a need for improvements in ease of attachment and detachment, wet and dynamic adhesion, and user convenience. , Previous attempts have been made to implant magnetic materials or add monotonous suckers to dentures, but there are still limits to their use due to additional procedures, side effects, and low wet adhesion. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, various studies based on biologically inspired adhesion mechanisms such as mechanical interlocking, capillary forces, and van der Waals forces driven by interfacial interactions are being conducted. , Although the excellent performance of recently developed reversible adhesive materials increases their applicability to wet biological surfaces such as skin and organs, the development of clean, reversible adhesive materials for oral surfaces with complex three-dimensional surfaces, dynamic masticatory activities, and variable wet environments remains a challenge. In particular, conventional technologies for attaching to the oral cavity, such as dentures, rely on chemical adhesive materials, but there is a need for improvements in ease of attachment and detachment, wet and dynamic adhesion, and user convenience. , Previous attempts have been made to implant magnetic materials or add monotonous suckers to dentures, but there are still limits to their use due to additional procedures, side effects, and low wet adhesion. , …”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous attempts have been made to implant magnetic materials or add monotonous suckers to dentures, but there are still limits to their use due to additional procedures, side effects, and low wet adhesion. 15,16 Beyond general structures, kirigami-based auxetic metastructures have a negative Poisson's ratio because the signs of the transverse and axial strains are the same; as a result, these structures expand in response to tensile strain. 17,18 The auxetic metastructure disperses the stress generated by deformation at the ligament, and studies have reported its application to dynamic and biological surfaces accompanied by movement.…”
Section: Introductionmentioning
confidence: 99%